Study of Combination of Guano and Humic Acid Fertilizer on Growth and Yield of Caisim Mustard Plants (Brassica chinensis Var. Parachinensis) - Al Rohmad, Habbib; Thohiron, Mochamad; Herawati, Jajuk (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
The purpose of this study was to determine whether the combination of guano and humic acid fertilizers affects the growth and yield of caisim mustard plants. This study was conducted in the Sememi Surabaya People's Forest Park. The study took five months from December 2023 to May 2024. This study was conducted with a Completely Randomized Design, consisting of two treatment factors, namely (I) Guano fertilizer dose and (II) Humic Acid dose with five samples and three replications. The concentrations used were: (Go) guano dose 0 grams; (G1) guano dose 20 grams per polybag; (G2) guano dose 40 grams per polybag; (G3) guano dose 60 grams per polybag; and the doses of humic acid used were: (Ho) humic acid dose 0 grams per polybag; (H1) humic acid dose 25 grams per polybag; (H2) humic acid dose 50 grams per polybag; (H3) and a dose of humic acid of 75 grams per polybag. Based on research on the study of the combination of guano and humic acid on the growth and yield of caisim plants (Brassica chinensis var. Parachinensis) from the G3 treatment (60 grams per polybag) showed the best treatment for all parameters, while the humic acid treatment H1 (25 grams per polybag) was the best treatment for all parameters.